Kajian Sistematis Khasiat Empiris dan Farmakologis Formula Herbal Bu Zhong Yi Qi Tang - Aryaprana Nando; Hari Iskandar Kang; Suryawan Suryawan; Yelini Fan Hardi; Wijono Sukaputra Agussalim (Institut Nalanda, 2023)
Background: Bu Zhong Yi Qi Tang (BZYQT) is a classic traditional chinese medicine herbal formula with tonic property which is used widely by the people. Scientific researches have been done abundantly to explore the empirical claims of BZYQT in line with its pharmacologic effects. Methods: This article is a systematic review of published evidences about the empirical and pharmacological effects of BZYQT available from Sciencedirect, PubMed and CNKI data bases. Results: BZYQT has been empirically used as a central Qi tonic or energy enhancer. Pharmacologic studies indicate its effects encompass regulating various aspects of gastrointestinal function, antitumor effects, immune stimulant, and others. Conclusions: The empirical effects of BZYQT have been proven scientifically in regulation of various gastrointestinal functions, immune stimulation, antitumor, and others.